Survei Proses Kegiatan Belajar Mengajar Guru PJOK di Masa Pandemi Covid-19 - Fitra Ramadhan; Syafaruddin Syafaruddin; Ahmad Richard Victorian (Universitas Negeri Padang, 2021)
Learning and teaching are two things that are closely related and cannot be separated in eductive activities. learning and teaching is said to be a form of education which creates an interaction between teachers and students. The purpose of this study was to determine how well the teaching and learning activities of PJOK teachers were carried out during the Covid-19 pandemic at State Senior High Schools and Vocational High School in Pangkalpinang City, the province of the islands of Bangka Belitung. This research is a descriptive quantitative approach. The subjects of this study were all State Senior High School and Vocational High School in Pangkalpinang City consisting of a population of 10 schools and a sample of 10 PJOK teachers as well as total sampling technique. The instrument in this study used a validated questionnaire. Quantitative descriptive data analysis techniques with percentage data. The results of this study indicate that the teaching and learning process of PJOK teachers during the Covid-19 pandemic at Public Senior High School and Vocational High School in Pangkalpinang City in the conditions of the Covid-19 pandemic all teachers 100% continued to carry out PJOK learning. Whereas in the learning method of the teaching and learning process of PJOK teachers during the Covid-19 pandemic, 90% of the teachers used online learning methods and 10% only gave homework. From these results it can be concluded that the teaching and learning process of PJOK teachers during the Covid-19 pandemic at Public Senior High School and Vocational High School in Pangkalpinang City is still given and continues to be carried out.